185k views
2 votes
PLEASE HELP QUICK!!! 3x − 2(6 − x) = 7x + 2(5 + x) − 6

2 Answers

4 votes

Answer:

x = -4

Explanation:

3x -2(6-x) = 7x +2(5+x) -6

Distribute -2 through the parentheses 3x -12 +2x = 7x +2(5+x) -6

Distribute 2 through the parentheses 3x -12 +2x = 7x +10 +2x -6

3x -12 +2x = 7x +10 +2x -6 cancel equal terms on both sides of the equation

3x -12 = 7x +10 -6 subtract the numbers 3x -12 = 7x +4

Move variable to the left left handed side and change its sign

3x -7x-12 = 4 --> 3x -7x = 4 + 12 --> -4x = 4+12 --> -4x = 16

Divide both sides of the equation by -4 --> x = -4

User TDG
by
5.6k points
5 votes

Answer:

it would be x=-4

hope i helped ya

User Alex Payne
by
4.7k points